Answer:
(- 4, - 10 )
Step-by-step explanation:
Given the 2 equations
y = x - 6 → (1)
x = - 4 → (2)
Substitute x = - 4 into (1) for corresponding value of y
y = - 4 - 6 = - 10
Solution is (- 4, - 10 )
Answer:
PERIOD
Step-by-step explanation:
In order to answer the question, it's absolutely essential to have
enough of a description of the object to know which of its parts
'X', 'Y', and 'Z' are, and what other parts it may have.
An ideal way to accomplish this would have been for you to include the
picture that accompanies the question, wherever you copied it from.
Answer:
1840
Step-by-step explanation: